2001
DOI: 10.1103/physrevlett.87.266103
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Water Dissociation onTiO2(110)

Abstract: Scanning tunneling microscopy has been used to identify the adsorption site of H(2)O on TiO(2)(110)-(1 x 1) at 150 K, and to monitor the site of the dissociation products at 290 K. Water adsorbs onto the rows of fivefold coordinated Ti atoms at 150 K, dissociating by 290 K to form bridging but not terminal hydroxyls. This points to the involvement of bridging O vacancies in the dissociation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

27
261
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(290 citation statements)
references
References 12 publications
27
261
0
2
Order By: Relevance
“…13,22 The majority of experimental work supports the view that molecular adsorption dominates in the first layer of water ( 1 ML) on nearly perfect surfaces at low temperatures (<350 K), and that water dissociates only at oxygen vacancy sites. [23][24][25][26][27][28][29][30][31][32][33] The evidence for this picture includes ultraviolet photoelectron spectroscopy (UPS) measurements by Kurtz et al 23 of the nearly perfect (110) surface, which was interpreted in terms of molecular adsorption at monolayer coverage (1 ML) at 160 K, dissociative adsorption at low coverage (∼0.1 ML) at 300 K, and suggested that the rate of dissociation is higher on defective surfaces. Two other UPS studies indicated dissociative adsorption at low coverage, but deduced that dissociation occurred only at oxygen vacancy defect sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,22 The majority of experimental work supports the view that molecular adsorption dominates in the first layer of water ( 1 ML) on nearly perfect surfaces at low temperatures (<350 K), and that water dissociates only at oxygen vacancy sites. [23][24][25][26][27][28][29][30][31][32][33] The evidence for this picture includes ultraviolet photoelectron spectroscopy (UPS) measurements by Kurtz et al 23 of the nearly perfect (110) surface, which was interpreted in terms of molecular adsorption at monolayer coverage (1 ML) at 160 K, dissociative adsorption at low coverage (∼0.1 ML) at 300 K, and suggested that the rate of dissociation is higher on defective surfaces. Two other UPS studies indicated dissociative adsorption at low coverage, but deduced that dissociation occurred only at oxygen vacancy defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…As a sequel, the conclusions made from experimental studies vary notably in relation to the extent of dissociation on the nearly perfect surface at various temperatures. 23,27,31 An alternative interpretation of this evidence, and, in particular, of the HREELS spectrum, was developed on the basis of firstprinciples molecular dynamics. 34 In the calculated hydrogen vibrational power spectrum, both water bond-bending δ(HOH) and O-H stretching v(OH) signals were present.…”
Section: Introductionmentioning
confidence: 99%
“…The basic physical and electronic structure of the most stable ͑110͒ surface has been well studied both experimentally 5,6 and theoretically, [7][8][9][10][11] and now, many investigations focus on defected surfaces, especially oxygen vacancies, [12][13][14] adsorption, 10,[15][16][17] or even adsorption onto defected surfaces. 18 -20 Due to their particular relevance to catalysis, many studies have also investigated the properties of adsorbed carboxylic ͑RCOOH͒ acids on the TiO 2 (110) surface.…”
Section: Introductionmentioning
confidence: 99%
“…As such, bridging hydroxyl groups formed by water dissociation in oxygen vacancy defects interfere with determining the extent of dissociation on regular Ti sites (3,(14)(15)(16)(17)(18)(19). A number of recent studies by a variety of techniques including X-ray photoelectron spectroscopy (XPS) (20), infrared reflection absorption (21), photoelectron diffraction (PhD) (22), and scanning tunneling microscopy (STM) (23)(24)(25) arrived at conflicting conclusions. Whereas the XPS and PhD studies concluded partial dissociation of water in the hydrogenbonded chains on Ti sites at higher coverages (20,22), others are in favor of molecular bonding (21,25).…”
mentioning
confidence: 99%